A complex between DYRK1A and DCAF7 phosphorylates the C-terminal domain of RNA polymerase II to promote myogenesis. Issue 9 (13th March 2019) - Yu, Dan; Cattoglio, Claudia; Xue, Yuhua; Zhou, Qiang
Abstract: The general transcription factor P-TEFb, a master regulator of RNA polymerase (Pol) II elongation, phosphorylates the C-terminal domain (CTD) of Pol II and negative elongation factors to release Pol II from promoter-proximal pausing. We show here that P-TEFb surprisingly inhibits the myoblast differentiation into myotubes, and that P-TEFb and its two positive complexes are eliminated in this process. In contrast, DYRK1A, another CTD kinase known to control transcription of a subset of genes important for development and tissue homeostasis, is found to activate transcription of key myogenic genes. We show that active DYRK1A exists in a complex with the WD40-repeat protein DCAF7 that stabilizes and tethers DYRK1A to Pol II, so that DYRK1A–DCAF7 can co-migrate with and phosphorylate Pol II along the myogenic gene loci. Thus, DCAF7 modulates the kinase signaling output of DYRK1A on Pol II to stimulate myogenic transcription after active P-TEFb function is shut off.